Threonine deaminase from Escherichia coli: feedback-hypersensitive enzyme from a genetic regulatory mutant. - Calhoun, D H (1976)
A mutation, ilvA538, in the gene coding for the biosynthetic L-threonine deaminase of Escherichia coli K-12 has previously been demonstrated to have pleiotropic regulatory effects leading to low and invariant expression of some of the isoleucine-valine biosynthetic enzyme, and altered expression of the branched-chain aminoacyl-tRNA synthetases. Strain PS187, which carries the ilvA538 allele, has a partial growth requirement for L-isoleucine and is characterized by a sensitivity to growth inhibition by L-leucine. The experiments reported here demonstrate that the L-threonine deaminase produced by strain PS187 is hypersensitive to inhibition by the pathway end product L-isoleucine. In addition, L-leucine, which acts at relatively high concentrations in vitro as an inhibitor of L-threonine deaminase from the wild type, is a more potent inhibitor of the activity of the mutant enzyme. Forty-six derivatives of strain PS187 were isolated as spontaneous mutants resistant to the growth-inhibitory effects of L-leucine. Two of these, strains MSR14 and MSR16, produce an L-threonine deaminase that is more resistant than the wild type to L-isoleucine inhibition, and intermediate between the wild type and strain PS187 with respect to L-leucine inhibition. Strains MSR14 and MSR16 produce L-threonine deaminase and dihydroxyacid dehydrase, the ilvD gene product, at the low levels characteristic of the parent strain. Other L-leucine-resistant derivatives of strain PS187 produce higher levels of the feedback-hypersensitive L-threonine deaminase. Thus, the sensitivity to growth inhibition by L-leucine observed with strain PS187 appears to be related both to the hypersensitivity of L-threonine deaminase to inhibition of catalytic activity and to the low level of ilv gene expression. The results reported here indicated that L-threonine deaminase is structurally altered in strain PS187, and thus provide further support for the proposal that L-threonine deaminase participates as a genetic regulatory element for the expression of the branched-chain amino acid biosynthetic enzymes.